PENGARUH KONSERVATISMA LABA TERHADAP KOEFISIEN RESPON LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dwi Apri Midiyanto; Yevi Dwitayanti (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2014)
Earnings response coefficient with conservatism financial statement appears due to thefinancial statement, particularly, a earning is a part that always is included in the financial statementcausing the market reaction.. This research is aimed at showing empirically the influence of earningconservatism toward the earning response coefficient of manufacture companies listed in IndonesiaStock Exchange (BEI).The method used in this research is quantitative analysis by an approach ofarithmetic calculation gained from secondary sources of an annual loss and earning statement whichis furthermore converted to SPSS version 16. The observation is done for 4 years long i.e. from2006 to 2009.The conclusion of the research shows that the earning conservatism affectssignificantly toward the earnings response coefficient. This means also that earning conservatismaffect the market about the earnings informed or published in the stock exchange.